2017
DOI: 10.1073/pnas.1706461114
|View full text |Cite
|
Sign up to set email alerts
|

Global priorities for conservation across multiple dimensions of mammalian diversity

Abstract: Conservation priorities that are based on species distribution, endemism, and vulnerability may underrepresent biologically unique species as well as their functional roles and evolutionary histories. To ensure that priorities are biologically comprehensive, multiple dimensions of diversity must be considered. Further, understanding how the different dimensions relate to one another spatially is important for conservation prioritization, but the relationship remains poorly understood. Here, we use spatial cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
180
2
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 233 publications
(197 citation statements)
references
References 60 publications
8
180
2
7
Order By: Relevance
“…Areas such as the Andes and Amazon in South America, and Madagascar, often emerge as high‐priority conservation areas for vertebrates (e.g., Brum et al, ; Pollock et al, ; Rosauer & Jetz, ). However, high‐priority areas for the conservation of other taxonomic groups may differ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Areas such as the Andes and Amazon in South America, and Madagascar, often emerge as high‐priority conservation areas for vertebrates (e.g., Brum et al, ; Pollock et al, ; Rosauer & Jetz, ). However, high‐priority areas for the conservation of other taxonomic groups may differ.…”
Section: Discussionmentioning
confidence: 99%
“…These approaches do not capture important facets of biological diversity, such as phylogenetic diversity or latent risk of extinction (see Daru, Bank, & Davies, ; Davies & Cadotte, ; Forest et al, ). Along these lines, studies have demonstrated that protected areas do not overlap with concentrations of avian or mammalian phylogenetic diversity (e.g., Brum et al, ; Pollock, Thuiller, & Jetz, ; Rosauer, Pollock, Linke, & Jetz, ). Given that some species have more distinctive evolutionary histories than others (Faith, ; Vane‐Wright, Humphries, & Williams, ), non‐random extinction of species can result in some clades losing a higher proportion of species than others (Davies & Yessoufou, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many such studies focus on taxonomic diversity (TD), which is often measured as species richness, that is, the total number of species in a community. However, the biodiversity concept includes many other aspects of biological variation, including genetic, functional, phenotypic, and phylogenetic variability, and the overlap of the priority regions across these diversity dimensions can be limited (Brum et al, 2017) Therefore, prioritizing conservation of hotspots of species richness can lead to loss of other facets of biodiversity (Veach, Minin, Pouzols, & Moilanen, 2017) in part because knowledge of species richness is insufficient to understand processes of species coexistence, community structure, and ecological function (Cadotte, Carscadden, & Mirotchnick, 2011;Pollock, Thuiller, & Jetz, 2017). However, the biodiversity concept includes many other aspects of biological variation, including genetic, functional, phenotypic, and phylogenetic variability, and the overlap of the priority regions across these diversity dimensions can be limited (Brum et al, 2017) Therefore, prioritizing conservation of hotspots of species richness can lead to loss of other facets of biodiversity (Veach, Minin, Pouzols, & Moilanen, 2017) in part because knowledge of species richness is insufficient to understand processes of species coexistence, community structure, and ecological function (Cadotte, Carscadden, & Mirotchnick, 2011;Pollock, Thuiller, & Jetz, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Historically, species richness has been used as a major criterion for determining conservation priorities (Van Jaarsveld et al, 1998). This has led to the advocacy of accounting for multiple dimensions of biodiversity including phylogenetic diversity (PD) and functional diversity (FD), in making conservation decisions (e.g., Brum et al, 2017). This has led to the advocacy of accounting for multiple dimensions of biodiversity including phylogenetic diversity (PD) and functional diversity (FD), in making conservation decisions (e.g., Brum et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation